Associations between death anxiety and fear of illness progression or recurrence: A protocol for a systematic review and meta-analysis - Tadgh Connery; Grazia D. Riotto; Daniel Macdonald; Rachel E. Menzies (PLoS ONE, 2025)
Background Fear of progression or recurrence of chronic physical illness has been associated with negative mental health outcomes across several conditions. Qualitative research suggests that the fear of death (i.e., death anxiety) may be associated with fear of illness progression or recurrence. However, a systematic evaluation of the relationship between fear of illness progression or recurrence and death anxiety is currently lacking. This protocol is for a systematic review of peer-reviewed, quantitative research examining associations between death anxiety and fear of illness progression or recurrence of chronic physical illnesses. Where possible, the strength of these associations will be tested through meta-analysis. Method A systematic search of quantitative studies written in English will be conducted across six academic databases: MEDLINE; PsycINFO; PubMed; Web of Science; CINAHL; EMBASE. Each record will be screened for eligibility by two authors. Data extraction and quality assessment, using the Joanna Briggs Inventory Risk of Bias tool, will similarly be performed by two authors, with discrepancies being resolved through discussion and consensus with a third author, REM. Data will be synthesised narratively, according to Cochrane guidelines, by which sample characteristics, measurement tools for both death anxiety and fear of illness progression or recurrence, and associations between death anxiety and fear of illness progression or recurrence will be described. Where sufficient data are available, meta-analysis will be conducted using Comprehensive Meta-Analysis Version 4. If there are sufficient studies (k = 4), additional analyses may examine whether the size of the relationship differs between illness types (e.g., life-threatening vs. non-life-threatening). Gender and age may also be examined as potential moderators of the effect, based on available reported data in the studies. The protocol has been registered in PROSPERO (CRD42024583393). Discussion This systematic review will further the understanding of how death anxiety and fear of illness progression or recurrence interact, and will help to shape future fear of illness progression or recurrence research with the aim of improving the wellbeing of individuals living with chronic physical illness.